Current Status and Future Challenges of the National Population Projection in South Korea Concerning Super-Low Fertility Patterns - Jun, Kwang-Hee; Choi, Seulki (한국인구학, 2010)
South Korea has experienced a rapid fertility decline and notable mortality improvement. As the drop in TFR was quicker and greater in terms of tempo and magnitude, it cast a new challenge of population projection - how to improve the forecasting accuracy in the country with a super-low fertility pattern. This study begin with the current status of the national population projection as implemented by Statistics Korea by comparing the 2009 interim projection with the 2006 official national population projection. Secondly, this study compare the population projection system including projection agencies, projection horizons, projection intervals, the number of projection scenarios, and the number of assumptions on fertility, mortality and international migration among super-low fertility countries. Thirdly we illustrate a stochastic population projection for Korea by transforming the population rates into one parameter series. Finally we describe the future challenges of the national population projection, and propose the projection scenarios for the 2011 official population projection. To enhance the accuracy, we suggest that Statistics Korea should update population projections more frequently or distinguish them into short-term and long-term projections. Adding more than four projection scenarios including additional types of "low-variant"fertility could show a variety of future changes. We also expect Statistics Korea topay more attention to the determination of a base population that should include both national and non-national populations. Finally we hope that Statistics Korea will find a wise way to incorporate the ideas underlying the system of stochastic population projection as part of the official national population projection. 한국사회가 최근 초저출산율이 지속되고, 사망율이 괄목할만큼 개선되면서 장래인구추계는 새로운 도전을 받고 있다. 이 연구는 장래 인구를 보다 정확한 예측하고, 양질의 정보를 제공하기 위한 방안을 한국의 경우를 중심으로 여타 저출산국가들가 비교연구를 통해 논의하였다. 구체적으로 이 연구는 1) 통계청이 실시한 2009년도 인구추계를 2006년도 공식 인구추계와 비교분석하였고, 2) 한국의 인구추계방식을 다른 나라의 경우와 비교 분석하였다. 비교에는 어떤 기관이 인구추계를 담당하는지, 얼마나 먼 장래까지 추계하는지, 얼마나 자주 행해지는지, 그리고 추계에 사용되는 출산, 사망, 이주에 관련된 가정과 시나리오의 수를 고려하였다. 3) 향후 50년간 장래인구를 확률적 인구추계 방식을 도입하여 예측해 보았다. 4) 마지막으로 2011년 장래인구추계에 사용될 시나리오를 살펴보았다. 이러한 논의를 바탕으로 이 연구는, 장래인구추계의 정확성을 높이기 위해서 인구추계를 좀더 자주 실시할 것과, 단기와 장기추계의 구분, 시나리오 수를 기존 네가지에서 더 늘릴 것을 제안하였다. 또한 기준인구 산정에 있어 국내 체류중인 외국인 인구을 고려할 것과 확률적 인구추계 방식도 도입할 것을 제안하였다.